Trudne początki polskiej inteligencji w I połowie XIX wieku (na przykładzie młodzieży galicyjskiej) - Kawalec, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Celem niniejszego tekstu jest ukazanie walki o zachowanie świadomości narodowej polskiej młodzieży z terenu Galicji w początkowych dekadach XIX w. wbrew polityce germanizacyjnej zaborcy. Główną formą niezgody na panującą sytuację społeczno-kulturalną była edukacja w duchu polskim. Kształcenie to skupiało się na samodzielnej nauce języka polskiego, poznawaniu literatury polskiej, historii narodowej, kultury, tradycji słowiańskiej, a konsekwencją tej działalności była oryginalna twórczość literacka i naukowa. Omówione zostaną warunki, metody i poziom austriackiego szkolnictwa, sposoby realizacji indywidualnych pasji młodzieży polskiej w okresie poprzedzającym powstanie listopadowe. Uczestnictwo młodzieży galicyjskiej w tym zrywie narodowym, a następnie zaangażowanie w ruchach politycznych o charakterze niepodległościowym z lat 30. XIX w. otwiera nową cezurę w utrwaleniu świadomości narodowej Polaków i Rusinów/Ukraińców.

The aim of this study is to present the struggle to preserve the national consciousness of Polish youth from the region of Galicia during the early decades of the 19 th century in spite of the Germanization policies implemented by the partitioning power. The main form of resistance to the prevailing socio-cultural situation was efforts aimed at education in the Polish spirit. This education focused on self-study of the Polish language, learning about Polish literature, national history, culture, and Slavic traditions, as well as on the creation of original literary and scholarly work. The present study discusses the conditions, mesthods, and level of Austrian schooling, as well as the ways in which Polish youth pursued their individual passions in the period preceding the November Uprising. The participation of Galician youth in this national uprising, and their subsequent involvement in political movements for independence in the 1830s, marks a new phase in the consolidation of national consciousness among Poles and Ruthenians/Ukrainians.
The difficult beginnings of the Polish intelligentsia in the first half of the 19 th century (as illustrated by the example of Galician youth)
Keywords: Galicja; germanizacja; młodzież polska; edukacja; język polski; Galicia; Germanization; Polish youth; education; Polish language